PERKEMBANGAN BUDAYA INDIS PADA BIDANG ARSITEKTUR DI MALANG RAYA TAHUN 1900-1942 - Jati Saputra Nuriansyah (Historiography: Journal of Indonesian History and Education, 2021)
In this article, we discuss the development of Indis culture in Malang Raya which influences the culture of society, especially in the field of architecture. The writing of this article was motivated by the existence of buildings that were influenced by Indis culture in Malang Raya in 1900-1942. The purposes of this article are 1) To know the history of Indis culture and its development; 2) To know Malang Raya as the new city of the Dutch East Indies; 3) To determine the cross between Indies and Javanese cultures in Malang Raya.Dalam artikel ini memuat tentang perkembangan budaya Indis di Malang Raya yang berpengaruh pada kebudayaan masyarakat, khususnya pada bidang arsitektur. Penulisan artikel ini dilatarbelakangi oleh adanya bangunan-bangunan yang mendapat pengaruh dari budaya Indis di Malang Raya pada tahun 1900-1942. Adapun tujuan dari penulisan artikel ini yaitu 1) Untuk mengetahui sejarah budaya Indis dan perkembangannya; 2) Untuk mengetahui Malang Raya sebagai perkotaan baru Hindia Belanda; 3) Untuk mengetahui persilangan budaya Indis dan Jawa di Malang Raya.